Facing Global Digital Revolution Proceedings of the 1st International Conference on Economics, Management, and Accounting (BES 2019), July 10, 2019, Semarang, Indonesia - International Conference on Economics, Management, and Accounting 2019 : Semarang, Indonesia); Nirmala Arum Janie, Dyah.; Dwi Mulyaningsih, Hendrati; Wahyu Rachmawati, Ani. (Milton : Routledge, 2020)
The Industrial Revolution 4.0 describes the exponential changes to the way we live, work, and relate to one another due to the adoption of cyber-physical systems, the Internet of Things, and the Internet of Systems. This revolution is expected to impact all disciplines, industries, business, and economics. Therefore, the main goal of the conference was to provide recent research related development of digital technology to the business, economics, management, and accounting field. These proceedings consist of selected papers, acceptedafter a rigid review process covering several issues in strategic decision making, management, accounting, policy studies, knowledge management, innovation management, applied economics, econometrics, capital market, and marketing & sales management. It will provide details beyond what is possible to be included in an oral presentation and constitute a concise but timely medium for the dissemination of recent research results. BES Conference Proceedings 2019 will be invaluable to professionals and academics in business, management, accounting, and economics for a good understanding of the developmentstowards industrial revolution 4.0.
Profiling the Work Force: Spearheading Human Capital Management in the Era of Industry 4.0 Innovation Strategy: How Answer the Challenges of the Digital Revolution Factor Afecting Good Governance On Performance Management The Use of Internet Media by Micro Banking Regional Owned Enterprises (ROEs); Evidence in Indonesia Capital Market Reaction on Commercial Aircraft Accidents Aggressive Financial Reporting, Board of Commissioners and Tax Aggressiveness: an Insight from Indonesia The Importance of Alumni Feedback in the Curriculum Evaluation Top Three Predominant Causes of Failure in Corporate Managership: Employees's Insights Conceptual Framework of Market Orientation and Firm Performance towards Manufacturing Sector: Moderating Effect of Innovation The Determinant of Building Construction, Property and Real Estate Companies Stock Prices in Indonesia
OCLC-licensed vendor bibliographic record.
Keywords: Economics -- Congresses; Strategic planning -- Congresses; Accounting -- Congresses; BUSINESS & ECONOMICS / General; BUSINESS & ECONOMICS / Accounting / Financial